UNGRAMATICAL NEGATION CONTRUCTIONS ON THE STUDENTS’ INDONESIA-ENGLISH TRANSLATION - Cenderato Cenderato; Exnasia Retno Palupi Handayani (Journal of English Educational Study (JEES), 2022)
This study was to investigate negation constructions in STAKat Negeri Pontianak students’ Indonesia-English translation. The participants were 78 students of semester 2, 4 and 6 in STAKat Negeri Pontianak in academic year 2021. The descriptive method was applied in this study in order to describe and analyze the constructions in negation. The tool of data collection was translation tes by preparing sentences in Indonesia and asking the students to translate them into English. There were 5 for each sentence in Present tense, Past tense, Modal, Progressive tense and Perpect tense. Based on finding, the students faced difficulties in demontrating the formula of each tense. Many of them still make ungramatical negation. The percentages of those are 80% in present perfect tense, 60.8% in past tense (60.8%), 50% in present progressive tense, 40.8% in present tense, and 29% occurs in modal. The highest ungrammatical constructions of singular case are tenses. The tenses mistake in present tense is 26.3% out of 40.8%, past tense is 55.9% out of 60.8%, present perfect tense is 70% out of 80%, present progressive tense is 47% out of 50%, and modal is 23.7% out of 29% ungrammatical negation construction.